The Development and Standardization of a Competing Sentence Test in Kannada - Hemalatha R (Journal of All India Institute of Speech and Hearing, 1970)
Jerger (1975),  proposed the subtlety principle,  which is  as follows The more centrally  the union  is located,  the more  subtle  is its manifestation. Hence to  diagnose  central  auditory  disorders (CAD)  auditory  tests need  to  be  very sophisticated. The conventional  audiometric test battery does not satisfy  this criteria. Several  authors  have attempted to develop  speech tests  which may  help  in the  diagnosis of CAD  problems  (Beasley  and  Freeman, 1977,  Bocca, Calero  and Cassinari, 1954;  Costello, 1977;  Jerger,  Speaks  and Trammel, 1968,  Katz,  1978; Matzker, 1959). Their  tests invariably use degraded speech material. Lynn and  Gilroy (1977) have  been  particularly successful in demonstrating the  clinical evaluation of  central  auditory  tests  in  the  diagnosis of  CAD. Willeford  and  Billger (1978),  found  that  children  with learning disabilities show poor performance on central  auditory  tests. The following test battery  was administered and  it was seen  that the children failed on  at least one subject.